Investigation of mechanical and superconducting properties of iron diffusion-doped Bi-2223 superconductors - Ozturk, O.; Cetinkara, H. A.; Asikuzun, E.; Akdogan, M.; Yilmazlar, M.; Terzioglu, C. (Springer Science and Business Media LLC, 2011)
The mechanical and superconducting properties of the Fe diffusion-doped (Bi-Pb)-2223 superconductor have been investigated. First, iron was evaporated on Bi-2223 superconductor and then the Fe layered superconductor was annealed at 830 °C for 10, 30 and 60 h. Static Vickers hardness, dc electrical resistivity, X-ray diffraction and scanning electron microcopy have been carried out to assess the effects of Fe doping. These measurements indicates that Fe doping, in comparison with the undoped samples, increased the critical transition temperature, and improved formation of high Tc phase, while decreasing the number and size of voids. Moreover, both microhardness and grain size were also enhanced by increasing the amount of diffusion. The values of microhardness were found to be load dependent. In addition, we have investigated the indentation size effect (ISE) behavior using some models such as the Kick’s law, modified proportional specimen resistance (MPRS) model and the Hays- Kendall (HK) approach. Among them, both HK and MPRS models are successful. In this study, the possible reasons of noticed improvement on mechanical and physical properties due to iron diffusion are discussed.
Keywords: Physical-Properties; Ceramics; Bi1.6pb0.4sr2ca2-Xsmxcu3oy Superconductors; Ca-Cu-O; (Nd,Eu,Gd)-Ba-Cu-O Bulk Superconductors; Grain-Boundaries; Single-Crystals; Hardness; Microhardness; Bi-2223; Au Diffusion